The DISSOLVING THE BOUNDARIES BETWEEN INSIDE AND OUTSIDE IN THE DESIGN OF THE CITY - Melgarejo Belenguer, María (Design/Arts/Culture, 2025)
How can cities be reinvented from the inside out? At the beginning we formulated this question as a starting point and understood that the dissolution of the boundaries between interior and exterior space opened up a new possibility for the design of the contemporary city. The idea of interior space becoming the public space of the city, borrowing from the concept of Inner Urbanism, emerged strongly as a design option for the city. This article explores new actions in the design of the built environment, such as the building being permeable to the urban fabric, that can be traversed, that can be seen from the outside, that generates new routes, new relationships, taking into account the behaviour of the user.